Mrs. Peachtree and the Eighth Avenue cat - Silverman, Erica; Beier, Ellen (New York : Aladdin Paperbacks, 1996)
In turn-of-the-century New York, a stray cat appears at Mrs. Peachtree's Eighth Avenue Tea Shop and becomes attached to the owner, despite her best attempts to resist it.
Booklist.
Horn Book.
School Library Journal.
3.5
K-3
Keywords: Cats -- Fiction; Cats -- Fiction